The distribution and zonation of barnacles around intertidal shores of Penang Island - Nurul H.H. Amir; Anita Talib; Omar Ahmad; Khairun Yahya (Syiah Kuala University, 2013)
The intertidal shores around Penang Island were surveyed for the distribution of barnacles from 14th November 2011 to 31st January 2012. The sampling was done by using 20 cm x 20 cm transect to count the barnacles. Three replicates were taken for each zonation available of the intertidal areas; i.e. upper, middle, and lower zonations, at every sampling site. From the result, three species were identified, including Euraphia withersi and Chthamalus malayensis from Family Chthamalidae, and Balanus amphitrite amphitrite from Family Balanidae. Chthamalus malayensis was found to be most abundant among the three species with 44.24% of total population; and Tg. Tokong recorded the highest abundance of this species (28.22%). This was followed by Euraphia withersi with 38.77%; which was found to be densely populated at Gelugor (21.92%). Balanus amphitrite amphitritewas least abundant with only 16.99% and mostly found at Gurney Drive (26.24%).The distribution of the three species of barnacles also varied among the sampling locations. Gertak Sanggul recorded the highest relative abundance of all three species of barnacles at 18.01%; while the location with the least relative abundance of barnacles is Queensbay with 0.33%.Based on ‘Non-Supervised Artificial Neural Network’ (ANN), distinct zonation was observed where Chthamalus malayensis was more dominant on the upper zonation; Euraphia withersi on the middle zonation; and Balanus amphitrite amphitrite on the lower zonation. The interaction betweenbarnacles with other barnacles leads to competitive exclusion and niche partitioning which created zonations among the species. Interspecies interaction that brought by predation also played a part in the distribution of barnacles. Apart from that, the distribution was affected by the sampling sites and humanactivities; such as embankment, land reclamation, and residential development.